Land Certification of Government Assets Resulted From Swap-Over (Ruislag) to Ensure Legal Certainty of Land Rights (Case Study: Execution Of Ruislag MAN 2 Kuningan) - Meiliyana, Fatma Nurzanah; Suhadi (Universitas Negeri Semarang, 2025)
This research aims to find out the procedure for land certification as a result of the land swap (ruislag) in the implementation of the ruislag between MAN 2 Kuningan and Ciawigebang Village, a more in-depth analysis of the issues and strategies made by the parties involved in the certification process to achieve legal certainty of land rights. This research employs a qualitative research method, drawing on an empirical legal research approach and a sociological perspective. The results of this study indicate that the process of land certification as a result of ruislag is included in the maintenance service of land registration data by the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning service standards and land regulations so that a certificate of use rights and a certificate of business use rights for four plots of land to replace the Ciawigebang MAN 2 Kuningan Village Treasury. The issues faced are related to administrative documents, designation of replacement land rights, and land conditions, because the distance between the ruislag process and land registration is quite long. Strategies made are cooperation between the parties, increasing the intensity of coordination between agencies, and reviewing regulations relating to the issuance of ruislag and registration of land rights. With these strategies, the certification process has become easier, thereby ensuring the legal certainty of land rights for rights holders.